2021
DOI: 10.3390/ma14206018
|View full text |Cite
|
Sign up to set email alerts
|

The Applicability of Die Cast A356 Alloy to Additive Friction Stir Deposition at Various Feeding Speeds

Abstract: In the current investigation, additive friction stir-deposition (AFS-D) of as-cast hypoeutectic A356 Al alloy was conducted. The effect of feeding speeds of 3, 4, and 5 mm/min at a constant rotational speed of 1200 rpm on the macrostructure, microstructure, and hardness of the additive manufacturing parts (AMPs) was investigated. Various techniques (OM, SEM, and XRD) were used to evaluate grain microstructure, presence phases, and intermetallics for the as-cast material and the AMPs. The results showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…FSD as a thermomechanical process is similar to friction stir welding (FSW) [ 29 , 30 , 31 , 32 ] and processing (FSP) [ 28 ] in heat generation, heat dissipation, and heat transfer mechanisms in the stir zone [ 33 , 34 , 35 ]. In the AA2011 AMPs, the heat is generated by dynamic contact friction (DCF) between the consumable tool and AA5083 substrate material.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…FSD as a thermomechanical process is similar to friction stir welding (FSW) [ 29 , 30 , 31 , 32 ] and processing (FSP) [ 28 ] in heat generation, heat dissipation, and heat transfer mechanisms in the stir zone [ 33 , 34 , 35 ]. In the AA2011 AMPs, the heat is generated by dynamic contact friction (DCF) between the consumable tool and AA5083 substrate material.…”
Section: Resultsmentioning
confidence: 99%
“…This process may continue until all the rod length is consumed and became insufficient for more deposition. The shape of the consumed tool tends to form a conical shape, as shown in Figure 2 c. For AA2011-T6 group specimens, careful processing parameters were selected based on our experience in the field and the published data [ 24 , 29 ] to produce additive manufacturing parts. The required heat input to friction stir deposit such a hard material limits the process parameters to be 1200 rpm as a spindle rotation rate with 3, 6, and 9 mm/min feeding speeds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, friction stir deposition (FSD) as an additive manufacturing technology is recommended by many authors to build multilayers of different materials on various substrates [ 28 , 29 , 30 ]. This technology is a suitable technique to produce metallic parts for the automobile and aircraft industries.…”
Section: Introductionmentioning
confidence: 99%
“…This technology is a suitable technique to produce metallic parts for the automobile and aircraft industries. It is also a thermomechanical process based on the FSW principles, by adding a mechanism of material feeding to deposit alloys [ 29 , 30 , 31 ] and composites [ 28 ]. Perry et al [ 32 ] concluded that the FSD path of AA2024 Al alloy at a 300 rpm tool rotational speed, 2 mm/s travel speed, and 0.85 mm/s feed rate reveals an almost fully recrystallized microstructure.…”
Section: Introductionmentioning
confidence: 99%